The importance of trademarks protection in Nigeria (2017)
This article examines the importance of trademarks in Nigeria and the need for the country to update its trademark law in line with the modern trend. The current legislation on trademarks in Nigeria is the Trade Marks Act which has been in existence since 19 without any substantial amendment and it is a replica of the United Kingdom Trade Marks Act, 1938. Trademark protection in Nigeria is still deficient in aspects such as service marks, trade dress and the non-recognition of other instances of trademark infringement. In terms of the Act, Nigeria recognises only identical or similar goods but it is lacking by not including other types of trademark infringement. This article examines not only service marks and trade dress but it also highlights that counterfeiting is a type of trademark infringement that should be appropriately addressed. Other types of trademark infringement include parallel importation and dilution but for the purposes of this paper, will be made to trademark counterfeiting. Also, the use and development of technology has made counterfeiting even mo dangerous. These areas are considered the core of any law on the protection of trademarks and this will be discussed in the article.